STRATEGI KEBANGKITAN EKONOMI TIONGKOK DAN PENDEKATAN LONG CYCLE TRANSISI KEKUASAAN POLITIK DUNIA - Yoga Suharman; Sugiarto Pramono (Universitas Wahid Hasyim Semarang, 2021)
The rise of China reflects the reality of international politics today. Even though its emergence has only been sequenced since at least the economic reforms in 1987, the commitment of the Chinese nation was able to bring it to its position as a dynamist and shaping the global political economy order. Economic leaps, technology, research, and even the military outperformed many European countries and is even said to have matched the United States. How the economic strategy and the implications of China's rise to global politics are the focus of the study in this paper. In order to answer this question, the author examines the approach of capitalism with Chinese characteristics and long cycle in world politics using qualitative methods that utilize interpretive analysis techniques and literature review. Based on the authors argue that China's economic revival cannot be separated from the international trade strategy and financial policies adopted by the country. Meanwhile, China's rise sparked a reaction from the guarantor of hegemonic stability, namely the United States. The dynamics of the relationship between the two major countries is still the center of debate in the study of the global political economy today. Keywords: long cycle, world politics, financial strategy, the shifting power, power shifting